IDENTIFICATION OF GROUNDWATER POTENTIAL IN MANOKWARI FORMATION IN AMBAN VILLAGE, MANOKWARI, WEST PAPUA USING VERTICAL ELECTRICAL SOUNDING 1-D - Ceni Febi Kurnia Sari; Anik Hilyah; Ishak S. Erari; Fajar K. Rohmala; Yoszi Mingsi Anaperta (Universitas Mataram, 2026)
Amban Village (Manokwari, West Papua) has promising groundwater potential, but it is underutilized due to the complex hydrogeology of Quaternary karst limestone, which features rapid fracture conduit flow, low surface permeability, and seasonal water scarcity. This study mapped subsurface aquifers using 1-D Vertical Electrical Sounding (VES; Schlumberger) at nine stations (ST1–ST9) near high-demand areas. Data were collected with an MAE C313-SEV meter (AB/2 = 1–60 m; 120 m depth) and inverted in IP2WIN, yielding 8–11-layer models with RMS errors of 4.82–24.80%. Conductive layers interpreted as aquifers (0.3–1059 Ω·m) occur at ST4–ST5 (26–30 m; 1–27 Ω·m), ST9 (23–47 m), shallow zones at ST6–ST8 (4–9 m), and deeper targets at ST1–ST2 (43–64 m), generally beneath a resistive cover that helps protect water quality and sustain yield. The observed resistivity-depth patterns indicate both free (unconfined) and confined aquifer systems typical of karst limestone environments. These findings provide a robust scientific foundation for identifying optimal well-drilling locations and developing sustainable groundwater management strategies in similar karst limestone regions. Pump testing and borehole drilling are strongly recommended to confirm aquifer productivity and hydraulic properties.